Bagaimana Peran Masyarakat dalam Mengantisipasi Dampak Negatif Aksi Klitih di Kalangan Remaja di Kota Yogyakarta - Fatmawati, Fifi; Kurnia, Heri (CV. Kurnia Grup, 2025)
Klitih is a form of teenage anarchism that is currently rampant in Yogyakarta. Klitih is identical to a group of teenagers who want to injure or paralyze their opponents with violence. The perpetrators of klitih actions also often injure their opponents with sharp objects such as knives, gears, samurai swords and the like. Klitih is a new term to refer to student or teenage brawls that have long been inseparable from occurring in the city of Yogyakarta and its surroundings. This study aims to find out two things. First, to find out the factors causing klitih carried out by klitih perpetrators in the city of Yogyakarta and second, to find out how much community involvement is in anticipating the occurrence of klitih actions among teenagers in the city of Yogyakarta.